Cervical Spinal Epidural Abscess Due to Mycobacterium tuberculosis without Osseous Involvement: A Case Report. Issue 3 (July 2016) - Esteves, Sofia; Catarino, Isabel; Robles, Diogo; Lopes, Daniel; Silva, Fernando; de Sousa, Carlos
Abstract : Case: We present a rare case of cervical spinal epidural abscess due to Mycobacterium tuberculosis without osseous involvement that was treated with decompression and arthrodesis in a 2-stage procedure. Conclusion: Spinal epidural abscess due to Mycobacterium tuberculosis is the least common of the various forms of spinal tuberculosis. This abscess represents a severe infection of the epidural space that can compromise neural elements and can require urgent surgical intervention to avoid permanent neurological deficits. Early diagnosis and early decompression remain the 2 most important predictors of a successful neurological outcome.